2017
DOI: 10.1245/s10434-017-5884-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Surgical Patients with Chordomas of the Cervical Spine: A Study of 52 Cases from a Single Institution

Abstract: Contiguous vertebral segments involved, intralesional surgical margin, without adjuvant radiotherapy, and incisional biopsy significantly increase local recurrence, while tumor location in the upper cervical spine significantly increases tumor-related mortality. Thus, computed tomography-guided fine-needle aspiration biopsy and total spondylectomy with marginal excision may improve survival of patients with cervical chordoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Consistent with previous findings, the exposed surgical margin is also a prognostic factor for chordomas. [15] However, sometimes the complete exposure of the tumor is very difficult. Thus, we introduce another technique.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous findings, the exposed surgical margin is also a prognostic factor for chordomas. [15] However, sometimes the complete exposure of the tumor is very difficult. Thus, we introduce another technique.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al . 25 , a study of 52 cases from a single institution with a mean follow-up of 50 months (median 31 months) and range of 1–228 months, found that contiguous vertebral segment involvement, intralesional surgical margin, lack of treatment with adjuvant radiotherapy, and incisional biopsy significantly increase local recurrence. While tumor location in the upper cervical spine significantly increases tumor-related mortality 25 , the CT-guided fine needle aspiration biopsy and total spondylectomy with marginal excision may improve the survival of patients with cervical chordoma 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The central tenet of surgical treatment of chordomas is obtaining wide‐margin, en bloc resection of tumor. It has been demonstrated that subtotal excision of chordomas results in significantly higher rates of local recurrence and shorter intervals of disease‐free survival . Furthermore, it has been shown that violation of tumor margins can result in seeding and recurrence along the surgical pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is currently the mainstay of therapy, and extent of tumor removal is arguably the most significant prognostic factor . Damage to nearby structures such as brainstem, spinal nerve roots, and blood vessels may preclude en bloc resection of cervical and clival chordomas, resulting in high rates of recurrence.…”
Section: Introductionmentioning
confidence: 99%